Tertiary education in a second language : a case study of the linguistic repertoires and experiences of multilingual students at a South African tertiary institution who previously had French as medium of instruction - Nieman, Catharina Marita (Stellenbosch : Stellenbosch University, 2021)
Thesis (MA)--Stellenbosch University, 2021.